Glucose evoked regulation of Na,K-ATPase activity in pancreatic beta-cells - Costa, A.C.R. (2009)
Glucose is the most important physiological insulin secretagogue. However, the mechanism of glucose-induced insulin release is not fully understood. The current dogma states that, in pancreatic -cell, glucose metabolism leads to an increase of ATP/ADP ratio, closure of ATP-sensitive K+ channels, membrane depolarization, opening of the voltage-dependent Ca2+ channels and Ca2+ influx which triggers insulin exocytosis. However, the role of other electrogenic systems, namely ionic pumps, to these events remains essentially uninvestigated. Na,K-ATPase, responsible for maintaining Na+ and K+ gradients across the plasma membrane, extrudes 3Na+ in exchange for 2K+, generating a net outward current; Thus changes in its activity may contribute to the ionic events regulating insulin secretion. Regulation of Na,K-ATPase activity by glucose remains unclear and controversial, and has never been determined in intact -cells. The aim of this work was to develop a method to characterize Na,K-ATPase activity in intact -cells and to evaluate whether glucose contributes to its regulation.